2022
DOI: 10.1007/s00405-022-07273-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic and microscopic tympanoplasty in patients with chronic otitis media

Abstract: Background To compare the results between type I tympanoplasty performed with transcanal endoscopic ear surgery (TEES) and microscopic ear surgery (MES) for treatment of chronic otitis media in a homogenous group of patients. Methods A retrospective study was performed in our department between January 2011 and January 2016 to review primary type I tympanoplasty cases with a subtotal perforation, an intact ossicular chain, a dry ear for at least 1 month, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
4
20
0
1
Order By: Relevance
“…Corresponding with previous studies, our metaanalysis found ET to have a comparable post-operative ABG closure to MT (MD 0.57 dB; 95% CI, À1.23 to 2.36; p = 0.54; I 2 = 78%). 2,8,9,30,31 Additionally, our study supports the findings of a previous systematic review by Manna et al 10 by demonstrating that ET has a significantly shorter operative time than MT (MD, À24.73 min; 95% CI, À38.56 to À10.89; p = 0.0005; I 2 = 98%) reducing patient exposure to general anaesthesia. Although substantial heterogeneity in reporting prevented metaanalysis of pain scores and complication rates, in general post-operative pain and complications were more common in the MT cohort in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Corresponding with previous studies, our metaanalysis found ET to have a comparable post-operative ABG closure to MT (MD 0.57 dB; 95% CI, À1.23 to 2.36; p = 0.54; I 2 = 78%). 2,8,9,30,31 Additionally, our study supports the findings of a previous systematic review by Manna et al 10 by demonstrating that ET has a significantly shorter operative time than MT (MD, À24.73 min; 95% CI, À38.56 to À10.89; p = 0.0005; I 2 = 98%) reducing patient exposure to general anaesthesia. Although substantial heterogeneity in reporting prevented metaanalysis of pain scores and complication rates, in general post-operative pain and complications were more common in the MT cohort in our study.…”
Section: Discussionsupporting
confidence: 90%
“…While TM closure is the primary surgical goal of tympanoplasty, approaches demonstrating superior improvements in hearing are more favourable to surgeons and patients alike. Corresponding with previous studies, our meta‐analysis found ET to have a comparable post‐operative ABG closure to MT (MD 0.57 dB; 95% CI, −1.23 to 2.36; p = 0.54; I 2 = 78%) 2,8,9,30,31 . Additionally, our study supports the findings of a previous systematic review by Manna et al 10 by demonstrating that ET has a significantly shorter operative time than MT (MD, −24.73 min; 95% CI, −38.56 to −10.89; p = 0.0005; I 2 = 98%) reducing patient exposure to general anaesthesia.…”
Section: Discussionsupporting
confidence: 90%
“…in which required data were extracted from the six studies (11,(18)(19)(20)(21)(22), and a simple average is obtained.…”
Section: Outcomes Of Interestmentioning
confidence: 99%
“…Twenty studies (60.6%) were undertaken in India, three studies (9.1%) in China, two studies (6.1%) each in Thailand and Bangladesh, and one study (3.0%) each in Korea, Nepal, Iraq, Italy, Egypt, and Pakistan. In terms of study design, 13 studies (11,19,20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) were randomized and 20 (7)(8)(9)(10)12,13,18,21,22,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) were nonrandomized. The inclusion and exclusion criteria of all studies are summarized in Supplementary Content 3, http://links.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation